Football's Greatest Heroes : the National Football Museum's Hall of Fame - Galvin, Robert with Bushell, Mark; Foreword by Charlton, Sir Bobby (London Chrysalis Books Group plc, 2005)
From Dixie Dean, Stanley Matthews and Billy Wright, to Paul Gascoigne, Garry Lineker and David Beckham, over the years Britain has produced a wealth of great football players that have won domestic, European and global trophies.
Include Colour Illustrations and Index
Keywords: Soccer -- Soccer players -- Great Britain